SYSTEM OF CALCULATION WITH WEIGHT REDUNDANSY FOR PROCESSING SPEED AD CONVERTORS OF SEQUENTIAL APPROXIMATION AND DIGITAL ANALOUGE CONVERTER ABLE FOR SELF-CALIBRATION - Azarov, Alexey; Reshetnik, Alexandr; Bogomolov, Sergey (Scientific Works of Vinnytsia National Technical University, 2015)
There had been given the review of calculation system with weight redundancy. There had been analyzed the peculiarities of theoretic and numeral calculation systems with weight redundancy. There had been analyzed the possibility of realization of AD converter and digital-analog converter with weight redundancy on the basis of nonredundant digital-analog converter. There had been shown the possibility of usage of calculation redundant systems with weight redundancy and artificial base on the basis of dual series witch allows to build redundant digital-analog converter on the basis of nonredundant dual digital-analog converter without the creation of specialized elementary base.